The effects of high-fat diet on implant osseointegration: an experimental study - Dundar, Serkan; Yaman, Ferhan; Ozupek, Muhammed Fatih; Saybak, Arif; Gul, Mehmet; Asutay, Fatih; Ozercan, Ibrahim Hanifi (Korean Acad Oral & Maxillofacial Surgery, 2016)
Objectives: In this study, we investigated whether a high-fat diet (HFD) affected the bone implant connection (BIC) in peri-implant bone. Materials and Methods: Four male rabbits were used in this study. Dental implant surgery was introduced into each tibia, and four implants were integrated into each animal. In both the normal diet (ND) group (n=2) and HFD group (n=2), 8 implants were integrated, for a total of 16 integrated implants. The animals continued with their respective diets for 12 weeks post-surgery. Afterward, the rabbits were sacrificed, and the BIC was assessed histomorphometrically. Results: Histologic and histomorphometric analyses demonstrated that BIC was not impaired in the HFD group compared to the ND group. Conclusion: Within the limitations of this study, we found that HFD did not decrease the BIC in rabbit tibias.
Keywords: Bone implant contact; Osseointegration; Titanium implants; High-fat diet; Histomorphometric analysis